FACTORS CAUSING STUDENTS’ DIFFICULTIES IN LEARNING ENGLISH AT SMA KRISTEN RANTEPAO - Pali, Nopianti; Sudarsi, Elim Trika; Pongsapan, Nehru (Teaching English as a Foreign Language Overseas Journal, 2024)
The purpose of this research is to know factors causing student’s difficulties in learning English at SMA Kristen Rantepao. This research used qualitative research. The data were collected through interviews. In this study, the researcher used snowball sampling. The subjects of this study were ten student’s at SMA Kristen Rantepao. Through the analysis of the data, it was found that there are several factors causing student’s difficulties in learning English at SMA Kristen Rantepao: internal factor; low learning motivation, students' interest in and attitudes, cognitive skills. External factor; teaching methods, learning facilities and media, the family and social environment. Based on the result above, the researcher concludes that there are internal and external factors causing student’s difficulties in learning English at SMA Kristen Rantepao as mentioned above.